1-(2-Methoxyphenyl)-2-{[2-(2-methoxyphenyl)hydrazinylidene](nitro)methyl}diazene - von Eschwege, Karel G. (International Union of Crystallography, 2012)
In the title compound, C(15)H(15)N(5)O(4), a nitroformazan derivative, the formazan unit is essentially planar with an r.m.s. deviation of 0.0204 (6) Å and adopts a closed syn,s-cis configuration with an intramolecular N—H⋯N hydrogen bond. The formazan plane makes dihedral angles of 4.32 (5) and 24.35 (5)° with the benzene rings. The dihedral angle between the formazan plane and the nitro group is 12.58 (8)°. In the crystal, C—H⋯O interactions connect the molecules into an inversion dimer.